The motives and determinants of organisational citizenship behaviour in the information, communication, and technology sector in South Africa - Beale, Nonyezi Chloe (Rhodes University, 2026)
Organisational citizenship behaviour (OCB), commonly referred to as extra-role behaviour, describes employees' voluntary efforts beyond their formal job specifications to support and contribute to organisational goals. This study examines the motives and determinants of OCB within South Africa's information, communication, and technology (ICT) sector, a rapidly evolving industry influenced by the Fourth Industrial Revolution. Using the Social Exchange Theory and Psychological Contract Theory, this research explores why employees engage in OCB and the factors that sustain these behaviours. A qualitative methodology was applied to this study, with thematic analysis applied to data collected and analyses from nine research participants. Findings reveal that intersecting factors, including loyalty and commitment, leadership, workplace community, training and development, and aspirations for professional growth within the organisation shape OCB. These elements highlight the reciprocal nature of OCB, where employees’ voluntary efforts contribute to organisational success while ensuring personal and professional fulfilment. The study concludes with reflections on the research process and recommendations for future studies on enhancing OCB in the South African ICT sector.
Keywords: Organizational citizenship behavior; Organizational commitment; Leadership; Information and communications technology